Funcionamiento y eficiencia de una torre modificada para inoculacion de esporas de hongos - Castaño Zapata, Jairo; Castellanos, G.; Jara, Carlos E.; Pastor Corrales, Marcial A. (1986)
The precision of a modified tower for Uromyces phaseoli spore inoculation was assessed. Main parts of the tower are described and a picture included. In the 1st expt., the effect of the deposition control of U. phaseoli spores was studied on the uniformity of deposition during deposition times ranging between 1 and 5 min, using an uredospore concn. of 20 mg. In the 2nd expt., 4 concn. (3, 6, 12, and 24 mg) and 2 deposition controls (1 min and no control) were used. With early deposition controlled during 1 min, the standard deviation was very low and remained constant during the 5 deposition times. However, when deposition was spontaneous, the standard deviation increased with increasing deposition times. The early control of inoculum deposition is important to reach uniformity in spore deposition/area unit. The analysis of variance for deposition concn. and control showed a high statistically significant difference. Duncan test for the av. of deposited spores/field indicates that the higher the concn. of spores inoculated, the greater the amount of spores deposited; the amount of spores deposited (70X) with the 3, 6, 12, and 24 concn. was 32, 62, 116, and 240, resp. This was a logarithmic increase, showing great precision with the use of the tower. By controlling early inoculum deposition during 1 min., spore deposition/field decreases 50 percent, approx., ranging from 153 to 72. Besides offering uniform inoculum precision and deposition, the tower is suitable for quantitative studies. (CIAT)